Designing for dissemination through community advisory board engagement in an implementation mapping process: A case study - Gabriella M. McLoughlin; Yerusalem Yohannes; Molly Kerstetter; Omar Martinez; Alex Dopp; Jennifer O. Fisher; Maura Kepper; Rachel G. Tabak; Ross C. Brownson (Journal of Clinical and Translational Science)
Abstract